Parabolic trough collectors for industrial process heat in Cyprus - Kalogirou, Soteris A. (My University, 2002)
The thermal utilization of solar energy is usually confined to domestic hot water systems and somewhat to space heating at temperatures up to 60 °C. Industrial process heat has a considerable potential for solar energy utilization. Cyprus has a small isolated energy system, almost totally dependent on imported fuels to meet its energy demand. The abundance of solar radiation together with a good technological base, created favorable conditions for the exploitation of solar energy in the island. The number of units in operation today corresponds to one heater for every 3.7 people in the island, which is a world record. Despite this impressive record no solar industrial process heat system is in operation today. The main problem for this is the big expenditure required for such a system and the uncertainty of the benefits. The objective of this work was to investigate the viability of using parabolic trough collectors for industrial heat generation in Cyprus. The system is analyzed both thermally and economically with TRNSYS and the TMY for Nicosia, Cyprus, in order to show the magnitude of the expected benefits. The load is hot water delivered at 85 °C at a flow rate of 2000 kg/h for the first three quarters of each hour from 8:00–16:00 h, 5 days a week. The system consists of an array of parabolic trough collectors, hot water storage tank, piping and controls. The optimum collector area for the present application is 300 m2, the optimum collector flow rate is 54 kg/m2 h and the optimum storage tank size is 25 m3. The system covers 50% of the annual load of the system and gives life cycle savings of about C£6200 (€10800). This amount represent the money saved from the use of the system against paying for fuel. The savings however refer to a non-subsidized fuel price, which will be in effect from 2003. The optimum system can deliver a total of 896 GJ per year and avoids 208 tons of CO2 emissions to the atmosphere. The effect of various design changes on the system performance was investigated. The E–W tracking system (collector axis aligned in N–S direction) was found to be superior to the N–S one. The required load temperature affects the performance of the system as for higher temperatures the auxiliary energy required is bigger. Also a number of variations in the load use pattern have been investigated and presented in this paper. It was found that the bigger the load (double shift, full hour use pattern) the bigger the collector area required, the greater the first year fuel savings and the greater the life cycle savings of the installation. This means that it is more viable to apply solar industrial process heat to higher energy consumption industries.
Keywords: Solar system; System optimization